Increasing Students' Motivation and Cognitive Learning Outcomes through the Application of Learning Media Physics Based on Snakes and Ladders Game in Class X SMA - Doni T. Baok; Ruth Novi Kornalia Mellu; Kostan D.F. Mataubenu (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
The purpose of this research is to increase students' motivation and cognitive learning outcomes through the application of physics learning media based on the game of snakes and ladders in senior high school class X related to the material of work and energy. The research method used is a pre-experimental type with a one-group pretest-posttest design research model. Data collection techniques are through test techniques for learning outcomes and questionnaire techniques for student motivation and responses. Data were analyzed based on paired sample t-test technique, N-Gain test, and percentage descriptive. The results of the research obtained an increase in students' cognitive physics learning outcomes based on the results of the t-count score smaller than t-table, a large increase of 38.39% (medium), student learning motivation increased from good category (78.63%) to very good (88.47%), while the students' responses were categorized as very good. Therefore, the use of snakes and ladders game media is effectively applied for learning in SMA class X on the material of work and energy.